Procoagulant Platelets: Mechanisms of Generation and Action - Podoplelova, N.A.; Nechipurenko, D.Y.; Ignatova, A.A.; Sveshnikova, A.N.; Panteleev, M.A. (Hämostaseologie, 2021)
During the past decades, it has been increasingly recognized that the major function of accelerating membrane-dependent reactions of blood coagulation is predominantly implemented by a subset of activated platelets. These procoagulant platelets (also called collagen- and thrombin-activated or COAT, coated, necrotic, although there could be subtle differences between these definitions) are uniquely characterized by both procoagulant activity and, at the same time, inactivated integrins and profibrinolytic properties. The mechanisms of their generation both in vitro and in situ have been increasingly becoming clear, suggesting unique and multidirectional roles in hemostasis and thrombosis. In this mini-review, we shall highlight the existing concepts and challenges in this field.
Keywords: procoagulant platelets; thrombosis; hemostasis